The Effect Of Operating Cash Flow And Net Profit On Cash Dividend In Index Companies Kompas 100 On The Indonesia Stock Exchange - STIRMAN, Ivone Gabriella; MORASA, Jenny; PUSUNG, Rudy (PT Keberlanjutan Strategis Indonesia, 2023)
Cash dividends are one of the benefits obtained by investors as a form of profit sharing generated by the company, the profits obtained from cash dividends are expected to provide more certainty than capital gains. This study aims to determine the effect of operating cash flow and net profit on cash dividends in kompas 100 index companies on the Indonesia Stock Exchange (IDX) during the 2019-2021 period. This research uses quantitative methods with an associative approach. Sampling was carried out using the purposive sampling method and obtained by 36 companies that are members of the compass index 100. The results showed that partially the operating cash flow did not have a significant effect on cash dividends, and net profit had a significant effect on cash dividends, while simultaneously operating cash flow and net profit had a significant effect on cash dividends